IMPLEMENTATION OF SERVICE MANAGEMENT BASED ON MAQASHID SHARIA AT HOSPITAL X : - Ekasari, Ranti; Najwa Khaeria; Fitriah Ihsani Sri Rejeki; Nurintan Utami; Nurul Inayah Tompo; Syahral Amini; Muh. Alif Al Imam (Homes Journal: Hospital Management Studies Journal, 2024)
Backround: Islamic hospitals are hospitals where the running program refers to maqashid ash-shariah which is the goal of health services in all aspects and forms of activity both in the field of management or services in terms of medical and nursing care framed and aimed at the intentions of the Islamic sharia. Objective: The purpose of this study was to determine the level of success of Service Management Implementation activities based on Shariah Principles at Hospital X. Methods: The type of research conducted is qualitative research where the method used is the interview method. Informants in this study are part of the hospital management structure and patients who get services at Hospital X. Results: The results found that in terms of Maqasyid Sharia, Hospital X has carried out treatment procedures by applying sharia standards that apply to staff and all patients, starting from the preservation of religion, soul, mind, offspring, to property. Conslusion: Safeguarding Religion, Safeguarding the Spirit, Safeguarding the Intellect, Protecting the Offspring, and Safeguarding the Property, they have met sharia standards.